Effect of Dimples/Protrusion Concavity on Heat Transfer Performance of Rotating Channel - Dinh, Cong-Truong; Le, Minh-Sang; Do, Cong Khanh-Duy; Chung, Duy-Hung (JST: Engineering And Technology For Sustainable Development, 2023)
The continuing increase in gas turbine inlet temperature requires additional heat transfer at the trailing edge. Therefore, a large amount of research has been carried out to find a highly efficient cooling process for gas turbine blades. Pin-fins have been widely used in the trailing edge of gas turbines to enhance heat transfer performance. Pin-fins also strengthen the structure between the inlet and outlet faces of the gas turbine. According to previous research, the flow structure and heat transfer characteristics are influenced by many parameters of the pin-fin array, especially the pin-fin shape, height, diameter as well as layout. In this study, instead of changing the structure of the pin-fin array, the work focused on the design of protrusion/dimple points on the leading and trailing edges. Numerical simulations using the SST (Shear Stress Transport) turbulence model were performed to investigate the effect of dimple/protrusion concavity on flow structure and heat transfer characteristics in a rotating channel with pin-fin array. The pin-fins are arranged staggered to each other. The results show that when changing the dimple/protrusion concavity on the leading and trailing edges combined with the rotation speed, the heat transfer efficiency changes positively.